(untitled) (Norwich, N.Y., 2008)
The 5th edition continues the format of earlier editions, with information on hazardous chemicals garnered from U.S. government sources and in some cases from publications from the UN and WHO. The entries are listed alphabetically by chemical name and include the formula, CAS number, RTECS number, regulatory authority and advisory bodies, hazardous waste characteristics, health hazard characteristics, flammability, reactivity, other hazards, and place within the hazard classification system. Details regarding shipping and spill handling are included and each entry concludes with a list of references. Appendices include lists of oxidizing materials, carcinogens, a glossary, a synonym and trade name cross index, and a CAS number cross index.
Keywords: Toxicology,Industrial toxicology